TRANSLATION AND STYLE PERCEIVED THROUGH THE COGNITIVE ROLE OF THE TRANSLATOR AS A TEXT RECEIVER DURING THE CREATIVE PROCESS - Atanasovska, Katarina Gjurchevska; Kimovska, Sonya Kitanovska (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This paper deals with the complexity of the relationship between translation and style. Bearing in mind that this topic has not been very much systematically researched sо far, the aim of the paper is to emphasise the importance of the cognitive role of the translator, who acts as a text receiver throughout the creative process of translating literary texts. The comparative analysis of translated literary texts form English into Macedonian accentuates the role and the significance of the text receiver (or the translator in this particular case) related to the perception of the stylistic dimension of the original text and to the way in which it is kept or lost in the translation, which affects its quality in general. This approach brings to the fore the translator’s role as a reader during the creative process and additionally tackles other issues like the style of the translation itself as a reflection of translator’s choices and its stylistic effect and impressions on other readers.